Share Price Reactions to Work-Family Initiatives: An Institutional Perspective - Arthur, Michelle M. (Academy of Management Journal, 2003)
This study of 130 announcements in the Wall Street Journal illustrated a significant, positive relationship between work-family human resource initiatives and share price. Institutional theory provided the theoretical underpinning for such a relationship. Share price reactions occurring both before and after ?legitimation? of a program were examined. As hypothesized, the work-family initiative and shareholder return relationship was higher in high-tech industries and, to a lesser extent, in industries with higher proportions of female employees. Implications of the results are discussed and suggestions for future research presented.